Influence of tides on melting and freezing beneath Filchner-Ronne Ice Shelf, Antarctica - Makinson, Keith; Holland, Paul R.; Jenkins, Adrian; Nicholls, Keith W.; Holland, David M. (Geophysical Research Letters, 2011)
[1] An isopycnic coordinate ocean circulation model is applied to the ocean cavity beneath Filchner‐Ronne Ice Shelf, investigating the role of tides on sub‐ice shelf circulation and ice shelf basal mass balance. Including tidal forcing causes a significant intensification in the sub‐ice shelf circulation, with an increase in melting (3‐fold) and refreezing (6‐fold); the net melt rate and seawater flux through the cavity approximately doubles. With tidal forcing, the spatial pattern and magnitude of basal melting and freezing generally match observations. The 0.22 m a−1 net melt rate is close to satellite‐derived estimates and at the lower end of oceanographic values. The Ice Shelf Water outflow mixes with shelf waters, forming a cold (<−1.9°C), dense overflow (0.83 Sv) that spills down the continental slope. These results demonstrate that tidal forcing is fundamental to both ice shelf‐ocean interactions and deep‐water formation in the southern Weddell Sea.